Cross sections for d-T neutron interaction with neodymium isotopes. (April 2015) - Luo, Junhua; An, Li; Jiang, Li; He, Long
Abstract: The cross-sections for ( n, x ) reactions with neodymium isotopes were measured at ( d - T ) neutron energies around 14 MeV with the activation technique. Samples were activated along with Nb and Al monitor foils to determine the incident neutron flux. Data are reported for the following reactions: 14 2 Nd(n, 2n) 14 1 Nd, 14 8 Nd(n, 2n) 14 7 Nd, 1 50 Nd(n, 2n) 14 9 Nd, 1 42 Nd(n, p) 14 2 Pr, 1 4 6 Nd(n, α) 143 Ce, and 1 46 Nd(n, p) 14 6 Pr. Theoretical calculations of excitation functions were performed with the TALYS-1.6 nuclear model code, at neutron energies varying from the reaction threshold to 20 MeV. The results were discussed and compared with experimental data found in the literature, and with the comprehensive evaluation data in ENDF/B-VII.1, JENDL-4.0, and CENDL-3 libraries. Highlights: The cross sections for the ( n, x ) reactions on Neodymium have been measured. Mono-energetic neutron beams using thed -T reaction; Energies: 13.5–14.8 MeV. Neutron cross-section measurements by means of the activation technique. Reference reactions 93 Nb(n, 2n) 92m Nb and 27 (n, α) 24 Na were used as the monitor. Nuclear reaction code TALYS-1.6 was used.